Today in San Francisco (27 May 2020) - Prigoff, Jim (Street Art & Urban Creativity, 2020)
After two and a half months of staying at home, I ventured to SF to make an important pick-up. I never got out of my car. I documented a few aspects of the trip which I thought I would share.